Validation of a new emotion regulation self-report questionnaire for children: research - Junghänel, Michaela; Wand, Hildegard; Dose, Christina; Thöne, Ann-Kathrin; Treier, Anne-Katrin; Hanisch, Charlotte; Ritschel, Anne; Kölch, Michael; Lincke, Lena; Roessner, Veit; Kohls, Gregor; Ravens-Sieberer, Ulrike; et al. (BMC psychiatry, 2022)
To examine and validate the self-report Questionnaire on the Regulation of Unpleasant Moods in Children (FRUST), which is a modified and shortened version of the Questionnaire for the Assessment of Emotion Regulation in Children and Adolescents (FEEL-KJ). The data comprised child and parent ratings of a community-screened sample with differing levels of affective dysregulation (AD) (N = 391, age: M = 10.64, SD = 1.33, 56% male). We conducted latent factor analyses to establish a factor structure. Subsequently, we assessed measurement invariance (MI) regarding age, gender, and AD level and evaluated the internal consistencies of the scales. Finally, we examined the convergent and divergent validity of the instrument by calculating differential correlations between the emotion regulation strategy (ERS) scales and self- and parent-report measures of psychopathology. A four-factor model, with one factor representing Dysfunctional Strategies and the three factors Distraction, Problem-Solving and Social Support representing functional strategies provided the best fit to our data and was straightforward to interpret. We found strong MI for age and gender and weak MI for AD level. Differential correlations with child and parent ratings of measures of psychopathology supported the construct validity of the factors. We established a reliable and valid self-report measure for the assessment of ERS in children. Due to the reduced number of items and the inclusion of highly specific regulatory behaviors, the FRUST might be a valuable contribution to the assessment of ER strategies for diagnostic, therapeutic, and research purposes.
Gesehen am 13.06.2023